Life cycle assessment of a floating photovoltaic system and feasibility for application in Thailand. (May 2021) - Cromratie Clemons, Sáde K.; Salloum, Coleman R.; Herdegen, Kyle G.; Kamens, Richard M.; Gheewala, Shabbir H.
Abstract: The performance of floating photovoltaics (FPV) was assessed by this study, a technology with rising popularity in the sustainable energy sector, by comparing its economic and environmental benefits to various types of photovoltaic technologies by utilizing Life Cycle Assessment (LCA) and Cost-Benefit Analysis. The largest impacts were shown from this LCA of a 150 MW FPV plant with a 30-year lifespan, which resulted from the roughly 73 kg of greenhouse gases and 110 m 3 s of water per MWh generated. Additionally, 21 reservoirs were considered in Thailand to house new FPV plants. Projected power generation scenarios varied between 0.64 GW and 13.28 GW when reservoir coverage percentages ranging from 1% to 20% were used. The Levelized Cost of Energy for several different photovoltaic systems yielded 0.24 USD per kWh for the FPV system, while the ground based polycrystalline and thin film systems were 0.43 USD and 0.54 USD per kWh, respectively. The payback period for FPV was 7.5 years, while for the polycrystalline and thin film it was 7.8 and 16.3 years. This combined with other factors made for a high return on investment for the FPV system. This study recommends a 10% coverage of 21 reservoirs throughout Thailand, allowing for potentially 6.52 GW of installed capacity, which would substantially help the country to reach their 2036 goal of having 30% of the energy mix from renewable sources. Highlights: Life Cycle Assessment was conducted of a floating solar plant in Thailand. A 150 MW plant was found to emit 73 kg of greenhouse gases per megawatt. The Payback Period for the floating solar plant was 7.5 years. Thailand could install between 0.64 and 13.28 GW at 21 reservoirs.